Pelatihan Pengembangan Komunikasi Pemasaran pada Produk Usaha Kelompok Pemberdayaan Kesejahteraan Keluarga Desa Cukangkawung, Kabupaten Tasikmalaya - Biki Zulfikri Rahmat; Elis Nurhasanah; Qini Shonia Az Zahra (Jurnal Pengabdian Pada Masyarakat, 2021)
MARKETING COMMUNICATION DEVELOPMENT TRAINING ON BUSINESS PRODUCTS OF FAMILY WELFARE EMPOWERMENT GROUP IN CUKANGKAWUNG VILLAGE, TASIKMALAYA REGENCY. This community service aims to assist partners in developing partner-owned businesses through marketing communications. Cukangkawung Village is rich in natural resources, one of which is processed from nature as a product that can be marketed and has the potential to compete in the market. However, this is constrained in marketing partner products. One of the problems is that marketing is still local in nature, does not have a brand and packaging is still plain. The condition of partner product packaging is still using clear plastic with staples attached and the copy product brand, of course this does not provide added value to partner products. Therefore, assistance is needed on how to market products, one of which is packaging that attracts consumers. So that the selling value of partner products increases. The results of the activity show change in increased knowledge and understanding of the potential, benefits, importance of packaging, digital marketing and promotional techniques. Through this service, products that have added value in promoting are created and supported by providing packaging and sealer for three partner groups in Cukangkawung Village, namely Molring in Cilogata village, snacks in Bangbayang and Harapan Mukti village business group.